Analisa Kerusakan Shaft Bottom Mold Pada Mesin Blowmolding Type Parker - Junaidi; M F Harahap; D Aswan (Jurnal MESIL (Mesin Elektro Sipil), 2023)
Blow Moldin`g Type Pa`rker is a` ma`chin`e for the process of formin`g products ma`de of pla`stic by in`jectin`g it first for the pla`stic feeder to be blown`. If sa`les a`re high, Pa`rker's Blow Moldin`g Type work is a`lso very high. Ma`in`ten`a`n`ce or ma`in`ten`a`n`ce of ma`chin`es a`n`d equipmen`t tha`t is ca`rried out is very n`ecessa`ry in` ca`rryin`g out production` process a`ctivities so tha`t they ca`n` run` smoothly. The resea`rch method used in` this resea`rch is the study of litera`ture a`n`d the a`pplica`tion` of preven`tive a`n`d corrective ma`in`ten`a`n`ce methods. The type of da`ma`ge tha`t often` occurs in` the Pa`rker type blow moldin`g ma`chin`e is the sha`ft bottom mold compon`en`t which often` gets a` liftin`g loa`d tha`t exceeds the idea`l ca`pa`city of the liftin`g loa`d. The results of this study a`re the ma`ximum liftin`g force of the sha`ft bottom mold is 1.87 ton`s with a` sha`ft len`gth of 25 cm with a` dia`meter of 2.5 cm a`n`d usin`g the type of preven`tive ma`in`ten`a`n`ce, n`a`mely ma`in`ten`a`n`ce to preven`t before the occurren`ce of da`ma`ge. Where the compa`n`y will pa`y for corrective ma`in`ten`a`n`ce of IDR 130,200,000 per yea`r. If compa`red, the compa`n`y will ta`ke preven`tive mea`sures of Rp. 62.160.000,- per yea`r, then` the differen`ce in` trea`tmen`t is Rp. 68.040.000,.